THE EFFECT OF SCIENTIFIC APPROACH ON SPEAKING COMPETENCY AND ITS RELATIONSHIP TO ACHIEVEMENT MOTIVATION OF TENTH YEAR STUDENTS OF SMK PARIWISATA TRIATMA JAYA BADUNG - Junipisa, Ni Made Ernila (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThis experimental study aims to investigate the effect of scientific approach and achievementmotivation on the speaking competency of tenth graders of SMK Pariwisata Triatma Jaya Badungin the academic year 2019/2020. This research applied 2x2 factorial design. Sixty students wereselected as sample through random sampling. Data on students’ speaking and achievementmotivation were collected by using multiple-choice tests. The acquired data were analyzedstatistically by Two Way Analysis of Variance (Two Way ANOVA) and Tukey test to know theinteraction effect at 5% significance level. This research discovers: 1) The scientific Approachsignificantly correlates with students’ speaking competency, 2) There is a significant interactioneffect of teaching strategy and achievement motivation on students speaking competency, 3) Thescientific Approach significantly correlates with the motivation students’ speaking competency,and 4) Conventional Strategy significantly correlates with low motivation students’ speakingcompetency.Keywords: scientific approach, achievement motivation, speaking competencyABSTRAKStudi eksperimen ini bertujuan untuk menginvestigasi pengaruh pendekatan saintifik dan motivasiberprestasi terhadap kompetensi berbicara siswa kelas X SMK Pariwisata Triatma JayaBadungpada tahun ajaran 2019/2020. Penelitian ini menggunakan rancangan 2x2 faktorial. 60siswa dilibatkan sebagai sampel penelitian. Mereka dipilih dengan teknik sampling acak. Datakompetensi berbicara dan motivasi berprestasi dikumpulkan dengan tes pilihan ganda. Data yangdiperoleh dianalisis dengan Analisis Varian AB (ANAVA AB) dan uji Tukey untuk mengetahuipengaruh interaksi. Temuan penelitian ini adalah (1) Pendekatan Saintifik berpengaruh secarasignifikan terhadap kompetensi berbicara siswa, (2) terdapat pengaruh interaksi yang signifikanstrategi mengajar dan motivasi berprestasi terhadap kompetensi berbicara siswa, (3) PendekatanSaintifik berpengaruh secara signifikan terhadap kompetensi berbicara siswa yang memilikimotivasi tinggi, dan (4) Strategi Konvensional berpengaruh secara signifikan terhadapkompetensi berbicara siswa yang memiliki motivasi rendah.Kata-kata kunci: pendekatan saintifik, motivasi berprestasi, kompetensi berbicara